Diagnosis and treatment of hepatic encephalopathy - Savlan, Ilona; Liakina, Valentina; Valantinas, Jonas (Acta medica Lituanica, 2013)
Background. Hepatic encephalopathy (HE) is a neuropsychiatric complication of liver cirrhosis which symptoms may vary from imperceptible to severe ones. In recent years, there have been some changes of fundamental hepatic encephalopathy pathogenesis and treatment. The early HE on the stage of minimal hepatic encephalopathy (MHE) is rarely diagnosed and treatable condition worldwide and in Lithuania as well, however, this HE stage is responsible for the cognitive disorders which impair the quality of life of cirrhotic patients. According to resent data, MHE can be diagnosed in up to 70% of cirrhotic patients. Aim. To evaluate new diagnostic and treatment strategies for HE and especially MHE for further use in clinical practice to cure the quality of life of cirrhotic patients and prevent clinical manifestation of HE. Methods and materials. This article is based on relevant original publications and reviews in English (1991–2012) that were retrieved by a selective key word based search in the Medline and PubMed databases. Results. It is recommended not to decrease an amount of proteins in food and consume products containing more branched-chain amino acids. Non-absorbable disaccharides (lactulose) are still the drugs of the first choice, though recent data show significant concerns about their effectiveness. Rifaximin is increasingly used all over the world for hepatic encephalopathy treatment. Other drugs for HE treatment are of secondary importance. Lactulose, probiotics are recommended for minimal hepatic encephalopathy treatment. Diagnosis, especially of minimal hepatic encephalopathy, remains complicated. There are no reliable and validated blood indicators to establish minimal hepatic encephalopathy diagnosis, and to follow up treatment efficacy. Psychometric and neurophysiologic methods, visualisation methods are used more in scientific researches. Computerized methods, such as inhibitory control and critical flicker frequency tests, are also promising. Conclusions. Further studies are necessary to design proper algorithms of hepatic encephalopathy diagnostic and treatment.
Keywords: hepatic encephalopathy; minimal hepatic encephalopathy; diagnosis; treatment